English Learners in STEM Subjects: Contemporary Views on STEM Subjects and Language With English Learners - Lee, Okhee; Stephens, Amy (Educational researcher, 2020)
With the release of the consensus report English Learners in STEM Subjects: Transforming Classrooms, Schools, and Lives, we highlight foundational constructs and perspectives associated with STEM subjects and language with English learners (ELs) that frame the report. The purpose here is to elevate these constructs and perspectives for discussion among the broader education research community. First, we provide an overview of the unique contributions of the report to move the ELs and STEM fields forward. Second, we describe ELs in terms of their heterogeneity and the inconsistency of educational policies that affect their learning opportunities in STEM subjects. Third, we describe contemporary views on STEM subjects and language with ELs that indicate that instructional shifts across STEM subjects and language are mutually supportive. Fourth, we describe promising instructional strategies to promote STEM learning and language development with ELs. Lastly, we close the article by reimagining STEM education with ELs and offer potential next steps. These foundational constructs and perspectives on STEM subjects and language with ELs are critical because they provide the conceptual grounding for the design of the education system for ELs. The report could contribute to building a knowledge base for ELs in STEM subjects and language as education research, policy, and practice converge to reimagine what is possible to both support and challenge ELs to learn academically rigorous content standards that are expected of all students.